Pedagogia histórico-crítica em Francisco Beltrão: caminhos e descaminhos (1990-2014) - Camargo, Tassia Lima de (2016)
This research lies in the field of the history of education and aims to investigate to what extent the design of Historic-Criticism Pedagogy, Marxist base, is being put into practice in educational institutions of Francisco Beltrão, in order to promote the arrest of scientific codes that favor a new interpretation of the world and a social practice transformed, once again, that by guidelines of State and Municipal Departments of Education, the Pedagogical Political Projects of schools appear based on this theory. To carry out the work in the use of documentary and bibliographic means and interviews. The text is divided into three chapters, the first attempts to understand the theoretical roots of the Historic-Criticism Pedagogy, from the conception of Marx, Lenin, Gramsci and Historic-Cultual Psychology of Vygotsky, we seek also to understand their goals and methodological foundations to from its main exponent, Teacher Dermeval Saviani. In the second deal of Historic-Criticism Pedagogy Network in the State of Paraná its principles and contradictions, through analysis of Paranaenses Educational Policy from 1990 to 2014. In the third chapter carries on about HCP in the Municipal Network of Francisco Beltrão, establishing relations with the political state comprising as they reflect the organization of municipal education. In addition to analyzing practices developed at the Municipal School XV October indicating that even this contradictory capitalist context there are some minor attempts at objectification of HPC. At the end of the survey we conclude that we have a lot to walk to the HPC pass a goal proclaimed in the documents and become a real goal. It was evident that we need to move from concrete conditions having clear that the story is built mediated by human actions and collective conscious and, therefore, it is fully possible to perform another education aimed emancipation of the working class.